Public health heritage and policy: HIV and AIDS in museums and archives - Manon Sian Parry (História, Ciências, Saúde: Manguinhos, 2020)
Abstract In the last five years there has been a resurgence of scholarly research and museum exhibitions on the history of HIV and AIDS. This work has called into question some of the conventions of archiving and interpreting the history of the pandemic. It is increasingly clear that a narrow range of materials have been saved. As historians and curators turn to these holdings for analysis and exhibition, they find they inadequately represent the impact of AIDS across diverse groups as well as the range of local, national, international responses. This essay considers some of the factors that shape collection of the material culture, particularly the heritage of public health, and the consequences for our understanding of lessons from the past.